Axiology of new technologies in public administration (Discourse of Law and Administration, 2024)
The aim is to present the role of public administration as an organisational and functional system in relation to the need and necessity for it to use different means of action. The aim is to show the relationship between the values which should guide the administration in fulfilling its role and the values attributed to the new technologies used by the administration. It seems that, at the current stage of development, both public administration and new technologies, in particular artificial intelligence, due to a certain autonomy of functioning and as a tool used by public administration, are linked to an emerging system of values. These values define and sometimes even determine the way in which public administration operates and achieves its objectives.
Keywords: axiology; values; new technologies; artificial intelligence; public administration